Implementasi Importance Performance Analysis Untuk Mengevaluasi Pelayanan Website Bank Umum Di Kota Batam - Welly Sugianto (Computer Based Information System Journal, 2015)
Importance performance analysis or IPA is a tool to evaluate and identify the major strengths and weaknesses of organization. This research attempts to understand the customer expectations and perceptions of website quality of a bank in batam city and shows the usefulness of the IPA in evaluating website quality attributes from customer perspectives in a bank. This research used 45 items from the website quality attributes and each item was rated using semantic scale. Responses were obtained from 280 usable questionnaires. The importance-performance analysis shows that 12 items fall into the “keep up the good work” quadrant, 9 items fall into the “concentrate here” quadrant, 9 items fall into the “low priority” quadrant, and 15 items fall into the “possible overkill” quadrant. The results of this research are useful in identifying areas for strategic focus to help organization develop the website quality strategies.